Analysis of the influence of the inter-wheel differentials design on the resistance of the car curved motion - Volontsevich, Dmitriy; Mormilo, Jakov; Veretennikov, Ievgenii (Eastern-European Journal of Enterprise Technologies, 2019)
The method and results of the analysis of the influence of the inter-wheel differentials design and the corresponding proportionality factors for the additional locking torque on the curved motion resistance of the four-wheel drive vehicle on paved roads are given. This allows choosing the most suitable designs for the parametric synthesis of the internally automated inter-wheel differential taking into account the results of studying the efficiency of different types of inter-wheel differentials under off-road conditions. Parametric optimization will allow synthesizing the internally automated inter-wheel differential, which would satisfy the requirements both to the vehicle cross-country ability and dynamics while not preventing the curved motion. In the process of modeling, the influence of the design and parameters of the inter-wheel differentials on power consumption in the motion with the given speed and trajectory, as well as on the actual turning radius of the vehicle, was estimated. According to the modeling results, it is concluded that it is possible to create a permanent internally automated inter-wheel differential based on differentials, in which locking degree depends on the squared difference in angular velocities of the semiaxles. For this, it is necessary to carry out optimization with respect to the proportionality factor of the locking torque, taking into account the limitations set forth in the work and using the described method of analyzing the influence of the inter-wheel differentials design on turning resistance. This will allow the effective operation of military and civil four-wheel drive vehicles both in difficult road conditions and on paved roads. In addition, the process of driving will not distract the driver to control the inter-wheel differentials, and the transmission will be performed without undue design complications.